Papua New Guinea Household Survey on Food Systems, 2018 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
In May – July, 2018, the International Food Policy Research Institute (IFPRI) implemented a rural household survey to investigate the food systems of rural households in four lowland areas of Papua New Guinea and how they assure sufficient food to meet the nutritional needs of their household members. The survey was implemented in East Sepik (Maprik), Sandaun / West Sepik (Nuku), and Madang (Middle Ramu) provinces (districts) and the Autonomous Region of Bougainville (ARoB - Buin and Siwai areas of Southern Bougainville). A total of 1,026 households were surveyed. The survey set out to achieve two goals: 1) use the household survey results to inform agricultural productivity, enhanced food security, child nutrition outcomes; and 2) collect baseline data for recently development programs supported by World Vision (WV). The rural household survey includes modules on: 1. Household characteristics (demographics, education, migration, etc.) 2. Agricultural production (crop production, use of household labor, etc.) 3. Household assets (production equipment and consumer durables, livestock ownership, and housing quality) 4. Income apart from own agricultural activities (wage employment, own business activities, and income transfers and gifts) 5. Consumption and expenditures (nonfood expenditures, food consumption, and dietary diversity) 6. Economic shocks and food insecurity (perceptions of poverty, recent food insecurity, and health and nutrition extension) 7. Gender roles and social expectations (asked separately for men and women) 8. Female health (pregnancy care and breastfeeding practices) 9. Child health (healthcare, vaccinations, and anthropometry)